The gastropod shell has been co-opted to kill parasitic nematodes - R. Rae (Scientific Reports, 2017)
Abstract Exoskeletons have evolved 18 times independently over 550 MYA and are essential for the success of the Gastropoda. The gastropod shell shows a vast array of different sizes, shapes and structures, and is made of conchiolin and calcium carbonate, which provides protection from predators and extreme environmental conditions. Here, I report that the gastropod shell has another function and has been co-opted as a defense system to encase and kill parasitic nematodes. Upon infection, cells on the inner layer of the shell adhere to the nematode cuticle, swarm over its body and fuse it to the inside of the shell. Shells of wild Cepaea nemoralis, C. hortensis and Cornu aspersum from around the U.K. are heavily infected with several nematode species including Caenorhabditis elegans. By examining conchology collections I show that nematodes are permanently fixed in shells for hundreds of years and that nematode encapsulation is a pleisomorphic trait, prevalent in both the achatinoid and non-achatinoid clades of the Stylommatophora (and slugs and shelled slugs), which diverged 90–130 MYA. Taken together, these results show that the shell also evolved to kill parasitic nematodes and this is the only example of an exoskeleton that has been co-opted as an immune system.